Liquid feed capable of stimulating gastric secretion of pigs and promoting nutrient absorption and utilization and preparation method of liquid feed - GAO SHAOBIN (2017)
The invention discloses liquid feed capable of stimulating gastric secretion of pigs and promoting nutrient absorption and utilization and a preparation method of the liquid feed. The liquid feed is prepared from the following raw materials in parts by weight: 720 to 780 parts of wheat middling, 74 to 76 parts of fructus perillae meal, 50 to 55 parts of cassava residue, 17 to 19 parts of fresh orange peel ferment, 0.6 to 0.8 part of polyethylene glycol, 1.3 to 1.5 parts of table salt, 12 to 15 parts of towel gourd protein powder, 1.2 to 1.4 parts of aloe glue, 56 to 58 parts of oatmeal, 2 to 3 parts of cherry juice, 0.2 to 0.3 part of lentinan, 1.2 to 1.4 parts of fennel seed, 38 to 42 parts of rice bran, 3 to 4 parts of semen euryales powder, 4 to 5 parts of leaf of poria cocos, 3 to 4 parts of apple flower, 8 to 10 parts of animal giblet powder, 0.3 to 0.4 part of grape seed oil, 0.4 to 0.5 part of activated lactobacillus powder, 0.12 to 0.15 part of sodium D-isoascorbate and 3 to 4 parts of gluten powder.